Genetic diversity of black mangrove (Rhizophora mucronata Lamk.) based on morphological markers in Maros, Pangkep, and Barru Provenances. Issue 1 (November 2021) - Mukrimin, M; Restu, M; DB, Evi Maria; Musdalifah, M
Abstract: Mangrove forests are tropical and subtropical forests that grow typically along the coast or river estuaries. Black mangroves are a type of mangrove found in South Sulawesi, precisely in Maros, Pangkep, and Barru Districts. The decline in black mangrove populations overcomes the threat limit to germplasm which can lead to reduced genetic diversity in black mangrove plants. To reduce the incidence of extinction in black mangroves, information on genetic diversity using one of the markers is required, namely morphological markers in taking samples of tree parts taken, namely the leaves, stems, and roots which are then for monitoring carried out in the Biotechnology Laboratory and tree breeding. The method used in this study is based on the literature on the development of the Tropical Fruit Descriptor information system. The results of the three studies proved that there is a difference between the evidence and the interprovenencies. The very close morphological kinship between them proved to be found in Pangkep. Pangkep's provenance has a high coefficient compared to the proof of Maros and Barru, which is at the time level of 70%, while the proof of Maros has the lowest coefficient compared to the proof of Barru and Pangkep, which is at the gathering level of 64%.